Sevoflurane Post-treatment Mitigates Oxygen-glucose Deprivationinduced Pyroptosis of Hippocampal Neurons by Regulating the Mafb/DUSP14 Axis - Chen, Chen; Zuo, Jianwei; Zhang, Huimei (Current Neurovascular Research, 2022)
Background: Ischemic brain injury often results in irreversible pyroptosis of neurons. Sevoflurane (Sevo) post-treatment exerts an alleviative role in neuroinflammation. Objectives: This work evaluated the mechanism of Sevo post-treatment in oxygen-glucose deprivation (OGD)-induced pyroptosis of rat hippocampal neurons. Methods: Rat hippocampal neuron cell line H19-7 cells were treated with OGD, followed by posttreatment of 2% Sevo. The expression patterns of Mafb ZIP Transcription Factor B (Mafb) and dual- specificity phosphatase 14 (DUSP14) were determined via quantitative real-time polymerase chain reaction (qRT-PCR) and Western blotting methods. H19-7 cell viability and the release of lactate dehydrogenase (LDH) were examined via the cell counting kit-8 and LDH assay kits. Levels of pyroptosis-related proteins and cytokines NOD-like receptor family, pyrin domain containing 3 (NLRP3), N-term cleaved Gasdermin-D (GSDMD-N), cleaved-caspase-1, interleukin (IL)-1β, and IL-18 were also examined. The binding relation between Mafb and the DUSP14 promoter was detected. Besides, the roles of Mafb/DUSP14 in OGD-induced pyroptosis of rat hippocampal neurons were investigated through functional rescue experiments. Results: Mafb and DUSP14 expression levels were decreased in OGD-induced hippocampal neurons. Sevo post-treatment up-regulated Mafb and DUSP14, facilitated H19-7 cell viability, inhibited LDH release, and reduced levels of NLRP3, GSDMD-N, cleaved-caspase-1, IL-1β, and IL-18. Mafb increased DUSP14 expression via binding to the DUSP14 promoter. Repressing Mafb or DUSP14 exacerbated pyroptosis of hippocampal neurons. Conclusion: Sevo post-treatment increased Mafb and DUSP14 expressions, which repressed OGDinduced pyroptosis of hippocampal neurons.
Keywords: DUSP14